The Social Environment and Business Communication in English: A Small-Scale Research on Front-Line Staff Performance in Russia, Spain and France - Rubtsova, Maria; Kapustkina, Elena; Karapetyan, Ruben; Kovalev, Ivan; Rasskazov, Sergey (International Review of Management and Marketing, 2015)
The performance measuring of the English everyday use of the front-line personnel remains an important topic of theoretical and practical study. Using a method of participant observation, the authors compared the St. Petersburg business environment with two cities in Spain (Madrid, Girona) and one in France (Perpignan). The observers carried out 64 visits in four cities. The sampling method is a convenience sample. The research in Spain and France was carried out in March-April, June-August 2014 and in Russia in June-July 2015. The observers checked how the front-line staff performed business communication in English. The authors draw conclusion that St. Petersburg demonstrates the worst results in the front-line interaction in English. Keywords: Front-Line Staff Performance, Business Communication in English, Assessment JEL Classifications: M12, M14, M53